Spectrophotometric determination of sparfloxacin in pharmaceutical formulations using bromothymol blue - Marona, HRN; Schapoval, EES (Elsevier B.V., 2001)
A visible light spectrophotometric method is described for them determination of sparfloxacin in tablets. The procedure is based on the complexation of bromothymol blue 0.5% and sparfloxacin to form a compound of yellow colour with maximum absorption at 385 nm. The Lambert-Beer law was obeyed in the concentration range of 2-12 mg/l. The present study describes a sensitive and accurate method for the determination of the concentration of sparfloxacin in tablets. It was also found that the excipients in the commercial tablet preparation did not interfere with the assay.
Keywords: fluoroquinolone; pharmaceutical analysis; sparfloxacin; visible light spectrophotometry